Do Learning Styles Affect Accounting Students’ Performance in Financial Management Online Courses? - Rosjidi, Anis Al; Mahfuroh, Riana (JABE (JOURNAL OF ACCOUNTING AND BUSINESS EDUCATION), 2023)
This study aimed to figure out whether learning styles affected the accounting students’ performance in the Financial Management online courses. This study was considered as experimental research using two groups of accounting students joining the Financial Management courses: one group attended online classroom, and the other group attended face-to-face classroom. Their learning styles were identified using the model of Fleming and Mills (1992). The student performance was measured using the final quiz scores. The accounting students with visual learning styles show no different performance in the face-to-face and online classrooms. Accounting students with auditory and kinesthetic learning styles show lower performance in the online classroom. Based on the results, the accounting programs and accounting lecturers should consider other teaching methods in teaching the financial courses to accommodate both auditory and kinesthetic learners. However, the accounting students’ performance in this study was only measured using the final quiz scores. Further research is needed to use more comprehensive performance measurements.